2001
DOI: 10.1177/00912700122010366
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Bioavailability of Quercetin Glycosides in Humans

Abstract: Due to its potentially beneficial impact on human health, the polyphenol quercetin has come into the focus of medicinal interest. However, data on the bioavailability of quercetin after oral intake are scarce and contradictory. Previous investigations indicate that the disposition of quercetin may depend on the sugar moiety of the glycoside or the plant matrix. To determine the influence of the sugar moiety or matrix on the absorption of quercetin, two isolated quercetin glycosides and two plant extracts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
417
5
12

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(459 citation statements)
references
References 30 publications
25
417
5
12
Order By: Relevance
“…Quercetin was excreted at an average of 1.1% of intake after onion consumption compared with 0.5% after tea, suggesting that quercetin from onions is more bioavailable than from tea. Recent studies have confirmed that the glycoside moiety is the major determinant of site of absorption of quercetin from the gastrointestinal tract, with quercetin rutinosides absorbed mainly from the colon and quercetin glucosides absorbed early in the small intestine (Morand et al, 2000;Olthof et al, 2000;Graefe et al, 2001). Kaempferol from endive was excreted at 1.9% of the amount ingested, which is comparable with the levels in urine shown by De Vries et al (1998), as their samples were taken after 7 days of an intervention study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Quercetin was excreted at an average of 1.1% of intake after onion consumption compared with 0.5% after tea, suggesting that quercetin from onions is more bioavailable than from tea. Recent studies have confirmed that the glycoside moiety is the major determinant of site of absorption of quercetin from the gastrointestinal tract, with quercetin rutinosides absorbed mainly from the colon and quercetin glucosides absorbed early in the small intestine (Morand et al, 2000;Olthof et al, 2000;Graefe et al, 2001). Kaempferol from endive was excreted at 1.9% of the amount ingested, which is comparable with the levels in urine shown by De Vries et al (1998), as their samples were taken after 7 days of an intervention study.…”
Section: Discussionsupporting
confidence: 64%
“…The intakes, plasma pharmacokinetics and urinary excretion of a few flavonoids and the soy isoflavones have been fairly extensively studied in man. For example, studies with quercetin have shown that various factors influence the amount absorbed, including the plant source and the type and linkage position of sugar(s) (Hollman et al, 1997(Hollman et al, , 1999Erlund et al, 2000;Graefe et al, 2001). Further, recent studies have shown that quercetin (and other flavonoids and isoflavones) are present in plasma and urine as a mixture of conjugated forms (methylated/glucuronidated/sulphated) Clark et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of flavanones in humans C Manach et al Manach et al, 1997). In humans, some enzymatic activities or transport systems facilitate the absorption of glucosylated quercetin in the small intestine, but seem ineffective for flavonoids linked to a rutinose (Hollman et al, 1999;Erlund et al, 2000;Graëfe et al, 2001). Rutinosides such as narirutin and hesperidin are thus probably absorbed in the colon after hydrolysis by the microflora.…”
Section: Discussionmentioning
confidence: 99%
“…They are on the order of 0.3-0.75 mmol/L after consumption of 80-100 mg quercetin equivalent administered in the form of apples, onions, or meals rich in plant products (Hollman et al, 1997;Graefe et al, 2001). Naringenin in grapefruit juice appears to be absorbed even better: a peak plasma concentration of 6 mmol/L is obtained after ingestion of 200 mg (Manach et al, 2004).…”
Section: Diet Diet Dietmentioning
confidence: 99%